Performance of Dual-Source CT in Calculi Component Analysis: A Systematic Review and Meta-Analysis of 2151 Calculi. Issue 4 (November 2021) - Yu, Juan; Zhou, Qingchun; Lin, Fan; Cui, Enming; Zhang, Han-wen; Lei, Yi; Luo, Liangping
Objective: To evaluate the performance of dual-source computed tomography (DSCT) in the component analysis of all types of calculi by doing a systematic review and meta-analysis. Methods: We searched MEDLINE, Embase, Scopus, and CNKI up to February 28, 2020, for in vivo studies investigating the performance of DSCT in the component analysis of calculi. We pooled the sensitivity, specificity, and areas under the summary receiver operating characteristic (AUROC) curves using a random-effect model in the meta-analysis. Publication bias was evaluated using Deek's funnel plot asymmetry test. Results: This analysis included a total of 37 studies in 1840 patients with 2151 calculi (462 uric acid [UA], 1383 calcium oxalate [CaOx], 55 cystine [Cys], 197 hydroxyapatite [HA], and 54 struvite [SV]). Using DSCT, the pooled accuracy for diagnosing UA (sensitivity, 0.95; specificity, 0.99), CaOx (0.98; 0.93), Cys (0.99; 0.99), HA (0.91; 0.99), and SV (0.42; 0.98) was calculated, respectively. The AUROC value was 0.99, 0.99, 1.00, 0.99, and 0.93, respectively. The P values for publication bias test were .49, .70, .07, .04, and .19, respectively. Conclusion: Dual-source computed tomography has high sensitivity and specificity for the component analysis of UA, CaOx, Cys, and HA calculi in vivo. This tool may have the potential to replace the current analysis tool in vitro in diagnosing calculi.